Geguritan Sebun Bangkung Kajian Bentuk, Fungsi Dan Makna - I Wayan Rinda Suardika (Institut Seni Indonesia Denpasar, 2007)
The research is aimed to find out the form, function, and the meaning of Geguritan Sebun Bangkung in social and cultural Hinduism community in Bali. in this research, the writer used structural theory, functional theory and semiotics theory. The structural theory is used to confirm the form, and the narrative structural of the literature, while the functional theory is used to analyze its function. In determining the meaning at the Geguritan Sebun Bangkung text, the semiotics theory is applied. These are methods used in this research: 1) In collecting data, it’s used library study, interview and completed with taking notes technique; 2) In analyzing data, qualitative descriptive method is used and completed with translation technique. After analyzing data, it’s found that Geguritan Sebun Bangkung contains 9 texts. Geguritan Sebun Bangkung consist of 16 pupuh which has followed its own rules (padalingsa: word rules, numerical rules and rhyme rule) in Medium Balinese language with some Old Javanese words.